(untitled) (Bangladesh Veterinarian, 2023)
The study aimed to evaluate the quality of fresh and frozen-thawed semen of five adult Holstein-Friesian crossbred bulls and the pregnancy rate of cows inseminated with frozen semen of those bulls. The fresh semen of breeding bulls collected for artificial insemination (AI) programme in the field was of good quality with volume (6.7 ± 0.2 ml - 8.9 ± 0.5 ml), concentration (904.2 ± 56.4 million/ml), mass activity (3.3 ± 0.2-3.6 ± 0.2), total motility (77.0 ± 1.1% – 92.1 ± 0.6%), progressive motility (67.0 ± 1.2% – 87.4 ± 0.6%) and semen viability (73.0 ± 0.6% to 85.4 ± 0.7%). The computer assisted sperm analysis (CASA) results showed that diluted pre-freezing semen had good sperm total motility (50.1 ± 3.8 % to 59.0 ± 4.7%), progressive motility (30.0 ± 1.2%-39.0 ± 1.6%), the velocity traits of straight linear velocity (VSL), curvilinear velocity (VCL) and average path velocity (VAP) of sperm ranged from 48.0 ± 1.3 - 71.3 ± 0.7 μm/s,118.1 ± 2.8-181.3 ± 10.9 μm/s and 68.4 ± 2.5 to 91.0 ± 2.9 μm/s, respectively. Bull 1 showed significantly higher VSL (71.3 ± 0.7 μm/s), VCL (181.3 ± 10.9 μm/s) and VAP (91.0 ± 2.9 μm/s) compared to others. Viability of frozen-thawed semen was lower in Bull 5 (73.0 ± 1.71%) compared to others. Although in frozen-thawed semen these parameters declined, the semen was sufficiently good to be used in AI in the field. The overall pregnancy rate using frozen semen was 55.6% and the highest pregnancy rate (62%) was in cows that were inseminated with frozen semen of Bull 1, but the differences between bulls was not significant. The pregnancy rate had positive correlation with sperm count, total motility, progressive motility, VCL, VSL, VAP, amplitude of lateral head displacement (ALH), beat cross frequency (BCF), linearity (LIN), straightness (STR), sperm viability. In artificially inseminated cows, the intensity of oestrus of cows, timing of AI, site of semen deposition and season had a significant effect on pregnancy rate. In conclusion, the fresh and frozen-thawed semen of breeding bulls supplied in North-East Bangladesh for AI programme were good quality. Heat detection and insemination timing need to be improved to increase the pregnancy rate. Bangl. vet. 2022. Vol. 39, No. 1-2, 1–15